2015
DOI: 10.1371/journal.pone.0143491
|View full text |Cite
|
Sign up to set email alerts
|

Deep Sequencing and Bioinformatic Analysis of Lesioned Sciatic Nerves after Crush Injury

Abstract: The peripheral nerve system has an intrinsic regenerative capacity in response to traumatic injury. To better understand the molecular events occurring after peripheral nerve injury, in the current study, a rat model of sciatic nerve crush injury was used. Injured nerves harvested at 0, 1, 4, 7, and 14 days post injury were subjected to deep RNA sequencing for examining global gene expression changes. According to the temporally differential expression patterns of a huge number of genes, 3 distinct phases were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
109
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(123 citation statements)
references
References 41 publications
13
109
1
Order By: Relevance
“…Our study, from the genetic aspect, confirmed the critical roles of macrophages during Wallerian degeneration. Moreover, our finding that inflammation and immune response was continuously activated is consistent with previous observation in a model of sciatic nerve crush injury (Yi et al, 2015). …”
Section: Discussionsupporting
confidence: 93%
“…Our study, from the genetic aspect, confirmed the critical roles of macrophages during Wallerian degeneration. Moreover, our finding that inflammation and immune response was continuously activated is consistent with previous observation in a model of sciatic nerve crush injury (Yi et al, 2015). …”
Section: Discussionsupporting
confidence: 93%
“…Curiously, olfactory transduction was the most enriched process among DE mRNAs in our study, which differs from the findings by Yi et al . in their RNA sequencing study . Furthermore, Olfr was involved in the response to stimulus, consistent with previous studies .…”
Section: Discussionsupporting
confidence: 88%
“…Because axon regeneration–specific genetic pathways governing metabolism and cell proliferation generally involve cytokine–cytokine receptor interaction pathways and cell cycle pathways, it is not surprising that these 2 pathways were significantly enriched among DE mRNAs. Intriguingly, in a parallel comparative analysis with RNA sequencing, the axon guidance pathway was consistently enriched among DE mRNAs in the early stages postinjury . Moreover, the early upregulated expression pattern of related mRNAs verified by PCR (Fig.…”
Section: Discussionmentioning
confidence: 75%
“…Interestingly, two of the enriched pathways, LXR/RXR, and acute phase response signaling, are involved in the regulation of immune responses. These findings are in agreement with the immunohistochemical staining of FFPE nerves tissues, that revealed the presence of immune cells at the injured site, and further extend at proteomic level previous observations that identified by gene expression analysis both pathways as significantly up‐regulated after nerve crush injury (Yi et al, ). At the level of protein synthesis, we found a highly significant enrichment of EIF2 signaling, suggesting an elevated rate of protein synthesis.…”
Section: Resultssupporting
confidence: 92%
“…Moreover, immunohistochemical analysis for monocyte/macrophage markers (CD11b, CD68), leukocyte marker (CD45), and T cell marker (CD3) showed markedly infiltrations of both monocyte and macrophages in the injured nerves (Figure c, uninjured vs. injured panels). This confirms other studies that described the presence of multiple cell types at the injured site, creating a cellular microenvironment that can improve the regenerative process (Yi et al, ).…”
Section: Resultssupporting
confidence: 90%